2019
DOI: 10.1097/mao.0000000000002352
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Metabolic Syndrome on the Prognosis of Idiopathic Sudden Sensorineural Hearing Loss

Abstract: Objectives: We aimed to verify the hypothesis that metabolic syndrome (MetS) and its components affect the prognosis of idiopathic sudden sensorineural hearing loss (ISNNHL). Study Design: A retrospective cohort study. Setting: Tertiary otology referral center. Patients: We divided patients who were diagnosed with ISSNHL between January 2015 and January 2018 into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…The prognosis of hearing loss and tinnitus is associated with other metabolic disorders, such as diabetes, hyperlipidemia, and hypothyroidism [166][167][168]. It was found that metabolic syndrome negatively affected the recovery of Chinese patients with idiopathic sudden sensorineural hearing loss [166].…”
Section: The Dilemma Of Inhibitory Downregulation In the Aging Centramentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of hearing loss and tinnitus is associated with other metabolic disorders, such as diabetes, hyperlipidemia, and hypothyroidism [166][167][168]. It was found that metabolic syndrome negatively affected the recovery of Chinese patients with idiopathic sudden sensorineural hearing loss [166].…”
Section: The Dilemma Of Inhibitory Downregulation In the Aging Centramentioning
confidence: 99%
“…The prognosis of hearing loss and tinnitus is associated with other metabolic disorders, such as diabetes, hyperlipidemia, and hypothyroidism [166][167][168]. It was found that metabolic syndrome negatively affected the recovery of Chinese patients with idiopathic sudden sensorineural hearing loss [166]. Moreover, a long history of hyperlipidemia was associated with the presence of a subtype of tinnitus that is characterized by a high rate of discomfort and inability to habituate [168].…”
Section: The Dilemma Of Inhibitory Downregulation In the Aging Centramentioning
confidence: 99%
“…Zhou et al [15], in a series of 228 patients affected by ISSHL, showed that MetS was associated with poorer hearing recovery; similar results were reported by Zhang et al [13] in 94 patients and Jung et al in 124 patients [14]. It should be noted that in all these studies obesity was evaluated with the BMI and not with the waist circumference.…”
Section: Plos Onementioning
confidence: 57%
“…Patients who showed <15 dB gain was considered "no improvement". In the present study as in Zhang et al [13], complete and partial recovery were defined as "recovered" and slight and no recovery were defined as "no recovered".…”
Section: Audiovestibular Investigationmentioning
confidence: 99%
See 1 more Smart Citation